Keratinocytes propagated in serum-free, feeder-free culture conditions fail to form stratified epidermis in a reconstituted skin model. - Rebecca Lamb; Carrie A Ambler (PLoS ONE)
Primary human epidermal stem cells isolated from skin tissues and subsequently expanded in tissue culture are used for human therapeutic use to reconstitute skin on patients and to generate artificial skin in culture for academic and commercial research. Classically, epidermal cells, known as keratinocytes, required fibroblast feeder support and serum-containing media for serial propagation. In alignment with global efforts to remove potential animal contaminants, many serum-free, feeder-free culture methods have been developed that support derivation and growth of these cells in 2-dimensional culture. Here we show that keratinocytes grown continually in serum-free and feeder-free conditions were unable to form into a stratified, mature epidermis in a skin equivalent model. This is not due to loss of cell potential as keratinocytes propagated in serum-free, feeder-free conditions retain their ability to form stratified epidermis when re-introduced to classic serum-containing media. Extracellular calcium supplementation failed to improve epidermis development. In contrast, the addition of serum to commercial, growth media developed for serum-free expansion of keratinocytes facilitated 3-dimensional stratification in our skin equivalent model. Moreover, the addition of heat-inactivated serum improved the epidermis structure and thickness, suggesting that serum contains factors that both aid and inhibit stratification.